Management of waqf rental by SRCs in Malaysia / Mohd Afandi Mat Rani …[et al.] - Mat Rani, Mohd Afandi; Sayin, Baharuddin; A. A, Asmah; Khalid, Mohammad Mahyuddin; Ab. Manan, Siti Khadijah (Academy of Contemporary Islamic Studies (ACIS), 2018)
Previous studies revealed several issues relating to the leasing of waqf properties in the aspects of the concepts and rulings, lease assessment rate, leasing contract and agreement. The overall management and administration of waqf property by State Religious Councils (SRC) are not yet discussed satisfactorily. This study therefore explored the practice of leasing of waqf properties by SRCs in Malaysia. Data and information for this study were collected through interviews and documented reports. Data were analysed based on inductive and deductive method. The study focused mainly on problems in the implementation and practice of waqf rental in Malaysia. The study found that there are still many shortcomings that the SRCs need to investigate seriously. It is proposed that a detailed study on waqf property management should be conducted for the sake of the ummah.